The Influence of Academic Supervision and Supervision on the Performance of Teacher Working Groups in Banyuasin III District, Banyuasin Regency - Hijerah Hijerah; Bukman Lian; Pahlawan Pahlawan (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to determine the effect of academic supervision and supervision on the performance of teacher working groups (KKG) in Banyuasin III District, Banyuasin Regency. KKG performance is very important in improving professionalism and the quality of learning in elementary schools. The research method used is quantitative with an associative approach. Data were collected through questionnaires distributed to KKG members, then analyzed using multiple linear regression. The results of the study indicate that academic supervision and supervision have a positive and significant effect on KKG performance. Structured supervision and effective academic supervision can encourage teachers to be more active, collaborative, and innovative in working group activities. These findings provide important implications for education managers in designing more optimal coaching strategies for teachers by improving the quality of academic supervision and supervision.